Teacher Training in Pakistan: Overview of Challenges and their Suggested Solutions - Kamran Akhtar Siddiqui; Shahid Hussain Mughal; Imran Ali Soomro; Masood Ahmed Dool (IJORER : International Journal of Recent Educational Research, 2021)
Education is a key component of progress in the present-day world. But this progress cannot be made without efforts of teachers. Therefore, teacher education, in particular teacher training becomes extremely important. In this regard, several trainings programs are initiated and executed across Pakistan but the desired outcomes have not been achieved so far. Hence, this study was conducted to explore the challenges in teacher training in Pakistan and the ways through which these issues can be resolved. The sources for the data of the study were the published studies in the field in the context of Pakistan, national education policy, and other relevant literature. Based on secondary data, the study concludes that the issues with teacher training in Pakistan are administrative as well as faculty related. The findings reveal that the challenges related to policy and planning, poor induction of teachers, lack of resources in teacher training institutions, demotivation among teachers, and unequal distribution of skilled and productive teachers, dual training system and infrequent trainings. These issues can be fixed by fostering encouraging environment, ensuring accountability and merit, providing necessary resources, systematizing professional training programs and their continuation. The findings of this study will, therefore, positively guide policymakers to develop the right and effective policy to improve the standard of teacher education in the country.